Evaluation of Disease Severity, Respiratory Muscle Strength, Respiratory Functions, Functionality, and Quality of Life in Patients With Upper Limb Lymphedema - Aydin, Gamze; Atici, Emine; Yarasir, Ezgi; Yentur, Songul Baglan; Elbasti, Muhammet Sahin (Cig Media Group, Lp, 2025)
Objective Lymphedema is a chronic, progressive disease that results from the accumulation of protein-rich fluid in the interstitial tissue spaces. The aim of this study is to assess disease severity, respiratory muscle strength, respiratory functions, pectoralis minor muscle shortening, functionality, and quality of life(QoL) in patients with upper limb lymphedema (ULL), and to compare these findings with healthy controls. Methods The disease severity was assessed using the Stillwell classification system; respiratory muscle strength was measured through maximum inspiratory and expiratory intraoral pressures (MIP, MEP, respectively); respiratory functions were evaluated with a spirometer; muscle length of pectoralis minor (PM) was measured with a tape measure; functionality was assessed using the Disabilities of the Arm, Shoulder and Hand (DASH); and QoL was evaluated with the Lymphedema Quality of Life Questionnaire - Arm (LYMQOL-Arm). The participants were divided into 2 groups, patients with ULL in Group 1; the healthy individuals were included in Group 2. Results The group 1 had lower values for MIP, MEP, FEV1, FVC, FEF25, FEF75, PEF, muscle length of PM, and DASH scores compared to group 2(p:0.018, p:0.010, P < .001, P < .001, p:0.001, p:0.043, P < .001, P < .001, P < .001, respectively). A negative correlation was found between disease severity and MIP, MEP, FEV1, FVC, and muscle length of PM (r:-0.598, r:-0.451, r:-0.458, r:-0.347, r:-0.498 (fair to good) respectively, P < .05). A positive correlation was observed between disease severity and LYMQOL-Arm (r:0.496 (good), P < .05). Conclusion Patients with ULL were found to be impaired in respiratory muscle strength, respiratory function tests, functionality and muscle length of PM compared to healthy individuals.
Keywords: Respiratory function test; Extremities; Lymphatic system; Lung function; Impairment